Supplier Selection Based on Green Procurement of Agricultural Commodities of Cassava: Environmental Perspective From Jember Regency - Danang Kumara Hadi; Assadam, Ahib; Widianto, Zidan Eka; Renadi, Berino (Journal of Soilscape and Agriculture, 2023)
Industrial developments and increasing consumer concern for the environment and the issue of environmentally sound industrial concepts have forced the industry to adjust the concept of green industries in every business, including in procurement, which is better known as green procurement. Supplier selection is an important decision-making problem to get suppliers who can increase the company's competitiveness. This research was conducted in Jember regency to evaluate and select cassava suppliers based on green procurement using the AHP method. The criteria used are 6 criteria, namely quality, technology capability, pollution control, environment management, green product, and green competence. Each criterion has sub-criteria between 3 or 4 sub-criteria. The number of sub criteria is used to determine the RI value. The RI value is used to calculate the CR value of each criterion. The results of data processing show that the highest CR value is in the technology capability criteria and the lowest CR value is in environment management. The highest hierarchical criterion value for environmental management criteria is 0.273, because the selection of cassava suppliers can be expected to pay attention to environmentally sound controls.